N-donor ligands enhancing luminescence properties of seven Zn/Cd(ii) MOFs based on a large rigid π-conjugated carboxylate ligand. Issue 47 (9th November 2015) - Ye, Run-Ping; Zhang, Xin; Zhai, Ji-Quan; Qin, Ye-Yan; Zhang, Lei; Yao, Yuan-Gen; Zhang, Jian
Abstract : Aggregation-induced emission (AIE) has been identified and studied based on a bulky π-conjugated ligand (H2 IDPA) with Zn/Cd II metals. Abstract : A series of Zn/Cd(ii ) coordination polymers, namely, [Zn(IDPA)(H2 O)] n · n (H2 O) (1 ), [Cd(IDPA)(bpp)] n · n (H2 O) (2 ), [Cd(IDPA)(4, 4′-bpy)1/2 ] n (3 ), [Zn(IDPA)(4, 4′-bpy)1/2 ] n (4 ), [Zn4 (IDPA)4 (phen)2 ·(H2 O)2 ] n ·2 n (H2 O) (5 ), [Zn(IDPA)(phen)·(H2 O)] n · n (H2 O) (6 ) and [Zn(IDPA)(2, 2′-bpy)·(H2 O)] n · n (H2 O) (7 ), have been prepared on the basis of a bulky 1, 3-benzenedicarboxylate derivative ligand, 5-(1-oxoisoindolin-2-yl)isophthalic acid (H2 IDPA), with the help of 1, 3-bis(4-pyridyl)propane (bpp), 4, 4′-bipyridine (4, 4′-bpy), 1, 10-phenanthroline (phen) or 2, 2′-bipyridine (2, 2′-bpy) as a secondary ligand. H2 IDPA is a luminous ligand with a large rigid π-conjugated system, and the solid-state luminescence properties of compounds1–7 have been comparatively investigated. The results indicate that their luminescence properties have been enhanced compared to those of the free ligand, especially for compounds2–7 which have been further regulated by N-donor ligands with a π-conjugated system. Compound2 is a 2D layer structure, and its quantum yield (QY) is 39.80%, which is much higher than those of the H2 IDPA ligand (QY = 4.41%) and compound1 (QY = 6.32%). From the viewpoint of crystal structure diversity and comparison, our results further demonstrate that ligands with a large π-conjugated system have a promotional effect on luminescence properties of coordination polymers.